The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13550-020-00722-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic network as an objective biomarker in monitoring deep brain stimulation for Parkinson’s disease: a longitudinal study

Abstract: Background With the advance of subthalamic nucleus (STN) deep brain stimulation (DBS) in the treatment of Parkinson’s disease (PD), it is desired to identify objective criteria for the monitoring of the therapy outcome. This paper explores the feasibility of metabolic network derived from positron emission tomography (PET) with 18F-fluorodeoxyglucose in monitoring the STN DBS treatment for PD. Methods Age-matched 33 PD patients, 33 healthy controls (HCs), 9 PD patients with bilateral DBS surgery and 9 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“… 22 Thus, our detection of increased OGI during the inter-ictal phase on the ipsilateral hemisphere to epileptic foci may help clinicians understand individual patients’ aetiology. While metabolic networks based on FDG-PET have sometimes been considered an objective biomarker for the assessment of certain treatments, 23 OGI appears to provide complementary information to glucose uptake, which may help locate or rank epileptic foci. In addition, of the three patients with poor outcomes (Engel class II or III), two of them had a bilateral disruption in relative OGI, whereas SEEG and SUV glc in those patients were only disrupted on one side (Supplemental Table S3).…”
Section: Discussionmentioning
confidence: 99%
“… 22 Thus, our detection of increased OGI during the inter-ictal phase on the ipsilateral hemisphere to epileptic foci may help clinicians understand individual patients’ aetiology. While metabolic networks based on FDG-PET have sometimes been considered an objective biomarker for the assessment of certain treatments, 23 OGI appears to provide complementary information to glucose uptake, which may help locate or rank epileptic foci. In addition, of the three patients with poor outcomes (Engel class II or III), two of them had a bilateral disruption in relative OGI, whereas SEEG and SUV glc in those patients were only disrupted on one side (Supplemental Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Two further studies [53,56] investigated a potential disease-modifying effect of DBS but did not report any significant results. Ge et al [53] examined PD-related metabolic covariance patterns (PDRP) after STN-DBS surgery but did not find any significant differences at 12 months of follow-up compared to baseline.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…Two further studies [53,56] investigated a potential disease-modifying effect of DBS but did not report any significant results. Ge et al [53] examined PD-related metabolic covariance patterns (PDRP) after STN-DBS surgery but did not find any significant differences at 12 months of follow-up compared to baseline. Hilker et al [56], found a significant decrease in the uptake of striatal 18F-dopa in PD subjects, thus revealing a decline in dopaminergic function even in PD subjects that were effectively treated with STN stimulation.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
See 2 more Smart Citations